MANAJEMEN SUMBER DAYA MANUSIA PENDIDIKAN ISLAM (UPAYA MENUNU MASYARAKAT EKONOMI ASEAN (MEA)) - Suhada Suhada (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
This paper aims to answer the question of how to develop human resource management in MI ICP Nurul Ulum LP Ma'arif NU Bojonegoro and MI Muhammadiyah 10 Bojonegoro in dealing with the Asean Economic Community? This type of research is a qualitative research. Data sources in the study were divided into two types, namely: primary in the form of direct interviews with the Head of MINU ICP Bojonegoro and the Principal of MIM 10 Bojonegoro and his staff who carried out the development of educator human resources, with the aim of digging deeper and getting the information needed in a detailed and thorough. While secondary sources are data sources that do not directly provide data to data collectors, for example through documents, photos and other matters relating to data needed by researchers at MINP ICP Bojonegoro and MIM 10 Bojonegoro. This research concludes that efforts to develop education human resources at MINP ICP Bojonegoro and MIM 10 Bojonegoro in facing the MEA era include: following the changing times, being active in training and wordshop, committed to educating the children of the nation, and thinking to advance in the future future.